1991
DOI: 10.1007/bf00225329
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of gas exchange and structure in birch leaves (Betula pendula) caused by low ozone concentrations

Abstract: Injury caused by low 03 concentrations (0, 0.05, 0.075, 0.1 gl 1-1) was analyzed in the epidermis and mesophyll of fully developed birch leaves by gas exchange experiments and low-temperature SEM: (I) after leaf formation in O3-free and ozonated air, and (II) after transferring control plants into ozonated air. In control leaves, autumnal senescence also was studied in O3-free air (III). As 03 concentration increased, leaves of (I) stayed reduced in size, but showed increased specific weight and stomatal densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
83
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 27 publications
13
83
0
Order By: Relevance
“…The higher stomatal density in clones A, D and E, and the lower stomatal conductance in our exposures agree with previous results for Betula pendula (Matyssek et al, 1991). Reduced stomatal conductance in response to ozone exposure has been found earlier also in Populus deltoides x trichocarpa (Reich & Lassoie, 1984), Gossypium hirsutum L. (Temple, 1986) and Populus maximowizii x trichocarpa (Pell, Eckardt & Enyedi, 1992) and therefore seem to be a consistent phenomenon related to ozone stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher stomatal density in clones A, D and E, and the lower stomatal conductance in our exposures agree with previous results for Betula pendula (Matyssek et al, 1991). Reduced stomatal conductance in response to ozone exposure has been found earlier also in Populus deltoides x trichocarpa (Reich & Lassoie, 1984), Gossypium hirsutum L. (Temple, 1986) and Populus maximowizii x trichocarpa (Pell, Eckardt & Enyedi, 1992) and therefore seem to be a consistent phenomenon related to ozone stress.…”
Section: Discussionsupporting
confidence: 92%
“…Reduced leaf biomass may be a result of disturbed photosynthesis and declined production, these being well known responses to ozone stress (e.g. Darrall, 1989;Matyssek et al, 1991;Pell et al, 1992), Ozone has been reported to cause a wide array of visible symptoms depending on the type and variety of plant, the concentration and duration of O3 exposure, and other interacting factors (Krupa & Manning, 1988). In birch, Matyssek e« a/.…”
Section: Discussionmentioning
confidence: 99%
“…It is now assumed that stomatal closure is not a direct effect of ozone, but a reaction to an increased internal CO # concentration resulting from the inhibition of carbon assimilation (Reich, 1987 ;Heath & Taylor, 1997). Several authors have reported oscillations in gas exchange and uncoupling of the relationship between A and g s (Matyssek et al, 1991 ;Flagler et al, 1994 ;Tjoelker et al, 1995 ;Clark et al, 1996) and have attributed this to loss of stomatal control ; this was not observed in the present experiment. Stomatal conductance in the elevated treatments was slightly reduced during the exposure period, but remained correlated with photosynthetic rates (K. Bortier, unpublished).…”
Section: mentioning
confidence: 46%
“…Gas exchange of leaves of different age classes from the main axis was measured shortly before harvest using an open gas-exchange system (Walz, Effeltrich, Germany) as described by Matyssek et al (1991). The rate of net photosynthesis was calculated according to von Caemmerer & Farquhar (1981) and was based on the one-sided leaf area which was determined with the Delta-T area meter MK2.…”
Section: Methodsmentioning
confidence: 99%